Boundaries in cyberpunk fiction : William Gibson's Neuromancer trilogy, Bruce Sterling's Schismatrix, and Neal Stephenson's Snow crash - Toerien, Michelle (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2000.